Plant Stress Physiology 2021
DOI: 10.5772/intechopen.92098
|View full text |Cite
|
Sign up to set email alerts
|

Consequences and Mitigation Strategies of Heat Stress for Sustainability of Soybean (Glycine maxL. Merr.) Production under the Changing Climate

Abstract: Increasing ambient temperature is a major climatic factor that negatively affects plant growth and development, and causes significant losses in soybean crop yield worldwide. Thus, high temperatures (HT) result in less seed germination, which leads to pathogenic infection, and decreases the economic yield of soybean. In addition, the efficiency of photosynthesis and transpiration of plants are affected by high temperatures, which have negative impact on the physio-biochemical process in the plant system, final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…Impact of climate change directly and indirectly on agriculture worldwide (Akram et al, 2018;Hashim et al, 2020;Kawo et al, 2021;Nasim et al, 2018;Sabagh et al, 2020). Climatic and environmental changes negatively influenced the health of the crops with the passage of time in the following ways: variations in the rainfall (Kimuku & Ngigi, 2017), extreme heat stress, change in the land surface temperature (LST), and migration of the peoples from rural to urban areas (Hussain et al, 2020a;Mukherjee & Singh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Impact of climate change directly and indirectly on agriculture worldwide (Akram et al, 2018;Hashim et al, 2020;Kawo et al, 2021;Nasim et al, 2018;Sabagh et al, 2020). Climatic and environmental changes negatively influenced the health of the crops with the passage of time in the following ways: variations in the rainfall (Kimuku & Ngigi, 2017), extreme heat stress, change in the land surface temperature (LST), and migration of the peoples from rural to urban areas (Hussain et al, 2020a;Mukherjee & Singh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture is a very essential sector, providing food to the rapidly increasing population in Punjab, the major agricultural province of Pakistan (Ahmad et al 2020;Sabagh et al 2020;Islam et al 2021). Agriculture can play a significant role in economic growth in the Punjab (Hussain et al 2020a;Mubeen et al 2021;Ahmed et al 2022;Naz et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that soybean plants adopt various pathways and mechanisms to cope with high-temperature circumstances. However, some recognized genes and pathways could be employed to improve heat tolerance in soybeans using molecular breeding approaches ( Sabagh et al, 2020 ). Future studies on the molecular mechanism of heat stress tolerance in soybean would identify the different genes and pathways controlling heat tolerance in soybean.…”
Section: Molecular Mechanism Of Heat Tolerance In Soybeanmentioning
confidence: 99%
“…Auxin was applied to soybean seeds which increased the germination percentage by increasing the biosynthesis of ABA ( Shuai et al, 2017 ). However, hormonal content alterations and signaling in soybean seed germination under heat episodes remain unclear and need further studies ( Sabagh et al, 2020 ). Ethylene (ET) is a main gaseous hormone that affects seed germination, growth and development, and fruit production under heat stress ( Meena et al, 2020b ).…”
Section: Use Of Phytohormones For Heat Tolerance In Soybeanmentioning
confidence: 99%